Knowledge, attitudes and eye health-seeking behaviours in a population-based sample of people with diabetes in rural China. Issue 6 (31st July 2020) - Chen, Tingting; Jin, Ling; Zhu, Wenhui; Wang, Congyao; Zhang, Guoshan; Wang, Xiuqin; Wang, Jun; Yang, Ke; Cochrane, Gillian M; Lamoureux, Ecosse Luc; Friedman, David S; Gilbert, Suzanne; et al.
Abstract : Aims: To assess knowledge of diabetes and acceptance of eye care among people with diabetes in rural China, to improve service uptake. Methods: Population-based study of people in Guangdong, China, with glycosylated haemoglobin A1c≥6.5% and/or known history of diabetes. Between August and November 2014, participants answered a questionnaire (based on Delphi process/previous focus groups) on medical history, demographic characteristics, self-rated health and vision, knowledge about diabetes and diabetic retinopathy, quality of local healthcare, barriers to treatment, likely acceptance of eye exams and treatment, and interventions rated most likely to improve service uptake. Presenting visual acuity was assessed, fundus photography performed and images graded by trained graders. Potential predictors of accepting care were evaluated and confounders adjusted for using logistic regression. Results: A total of 562 people (9.6% (256/5825), mean age 66.2±9.84 years, 207 (36.8%) men) had diabetes, 118 (22.3%) previously diagnosed. 'Very likely' or 'likely' acceptance of laser treatment (140/530=26.4%) was lower than for eye exams (317/530=59.8%, p<0.001). Predictors of accepting both exams and laser included younger age (p<.001) and prior awareness of diabetes diagnosis (p=0.004 and p=0.035, respectively). The leading barrier to receiving diabetes treatment was unawareness of diagnosis (409/454, 97.2%), while interventions rated most likely to improve acceptance of eye exams included reimbursement of travel costs (387/562, 73.0%), video or other health education (359/562, 67.7%) and phone call reminders (346/562, 65.3%). Conclusions: Improving diagnosis of diabetes, along with incentives, education and communication strategies, is most likely to enhance poor acceptance of diabetic eye care in this setting.